AI-DRIVEN DIGITAL STORYTELLING REDEFINING VISUAL NARRATIVES IN EDUCATION - Dubey, Shikha; Vekariya, Vipul; Gupta, Peeyush Kumar; Punia, Ankit; Nagpal, Manish; Aggarwal, Mohit (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Artificial Intelligence (AI) had become a radical force in digital storytelling and it was reshaping the way visual storytelling had been produced and distributed in the educational sector. Although it was becoming more popular, there was a gap in the literature on the most effective AI methods to achieve better engagement, understanding and creativity in the learner. This paper had explored three AI-inspired methods namely (1) Natural Language Generation (NLG) and Narrative Intelligence to create adaptive stories; (2) Computer Vision and Generative Visual Synthesis to generate dynamic visual narrative and (3) Multimodal Emotion and Engagement Analysis to create emotional adaptations in real-time. The techniques were now relatively appraised in regard to prime educational aspects, such as creativity, flexibility, emotional involvement, and retention of learning. Experimental findings had shown that, NLG had been better at narrative coherence and contextual relevance whereas, visual synthesis had been better in conceptual visualization as well as learner immersion. Nevertheless, the multimodal emotion-analysis approach had shown an overall better performance with an average of 28-percentage-point better performance in the engagement and comprehension than the other approaches.